E-government information search by English-as-a Second Language speakers: The effects of language proficiency and document reading level. Issue 4 (July 2022) - Harvey, Morgan; Brazier, David
Abstract: A rapid increase in the use of web-based technologies – and corresponding changes in government and local council policies – in recent years, means that many vital services are now provided solely online. While this has many potential benefits, it can place additional burdens on certain demographic groups, some of whom may become considerably disadvantaged or even disenfranchised. This is particularly problematic for English-as-a Second Language (ESL) speakers, who are often immigrants or refugees and thus have a greater need to access these e-government services, and who may struggle to understand and assess the relevance of complex documents. In this work we investigate the search behaviours and performance of native English speakers and two different groups of ESL speakers when completing e-government tasks, and the effect of document readability/complexity. In contrast with previous work, our results show significant differences between groups of varying language proficiency in terms of objective search performance, time on task, and self-perceived performance and confidence. We also demonstrate that document reading level moderates the effect of language proficiency on objective search performance. The findings contribute to our existing understanding of how English language proficiency affects search for e-government topics, and have important implications for the future development of e-government services to ensure more equitable access and use. Highlights: Search behaviours/performance of native and ESL speakers on e-government tasks. Clear differences between native and ESL speakers. Less proficient ESL speakers spend significantly longer on tasks and performed worse. Also less likely to identify relevant docs if they had a high reading level. Native speakers, conversely, were more likely to bookmark more complex documents.